IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DALAM MENGEMBANGKAN MINAT, SIKAP DAN PERILAKU POSITIF SISWA - Aam Miludin; Dewi Yanti; Mansur (UNISAN JURNAL, 2024)
While the expected goals: To find out and explain the efforts made by educators in developing students’ interests, attitudes and positive behavior through character formation which in the end students will have good morals in the school environment and in society, To find out the obstacles that hinder in fostering children’s interest in the formation of children’s character at MTs Al Ikhsan Kalirejo, East Oku Regency, South Sumatra Regency, To find out the efforts to overcome obstacles that cause the child’s character to become increasingly distant from noble moral values even though he has attended school education.In this study the authors chose a type of qualitative research, namely the method of observation, interviews or document review. The reason is that adjusting this method is simpler when dealing with multiple realities, and this method directly presents the nature of the relationship between the researcher and the respondent, and this method is more sensitive and more able to adapt to the many sharpening of joint influences on the value patterns encountered.The results of the research on the implementation of character education in developing students’ interests, attitudes and positive behavior at MTs Al Ikhsan Kalirejo are: Competence in preparing lesson plans, Competence in describing the curriculum, Competence in conducting evaluations. Constraints in developing students’ interests, attitudes, and positive behavior at MTs Al Ikhsan Kalirejo, namely: Low madrasah interest. Public awareness is still low regarding the presence of educational institutions with Islamic nuances (MTs).Character Education